Faktor-faktor yang Berhubungan dengan Kecanduan Internet pada Siswa SMAN “X” Padang - Feri Fernandes; Aprini Yulian Sari; Mahathir (NERS Jurnal Keperawatan)
Biological, psychological and social changes in adolescents made teens experience health problems in the community. The ease of internet access nowadays made teens more vulnerable to internet addiction. This study focus on factors that influence internet addiction such as academic stres, family attachment and peer attachment. The purpose of the study was to determine the relationship between academic stres, family attachment, peer attachment andinternet addiction at SMAN “X” Padang. The study design used correlation with cross sectional approach. The population was teenagers at SMAN “X” Padang. A total sample of 284 adolescents was determined for this study Respondents were recruited using simple random sampling. Data were analyzed using Pearson. Result for academic stres showed that there wasa significant relationship, a strong relationship strength and a positive relationship with internet addiction (p = 0,000), family attachment indicated that there was a significant relationship, a moderate relationship strength, a negative relationship with internet addiction (p = 0,000), and peer attachment shows that there wasa very weak, significant relationship and negative direction to the internet addiction (p = 0,000). Academic stres was the most significant influence on internet addiction in teenagers at SMAN “X”Padang. To manage academic stres experienced by students it is important to conduct guidance and counseling services so that students get help reducing stres experienced by students and functions as students can be optimized.